An investigation of the relation between university students’ levels of internet addiction and multiple intelligences - Altunhan, Abdullah; Tazegül, Ünsal (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The aim of this study is to reveal the relationship between Multiple Intelligences and internet addiction levels of students at Mardin Artuklu University. The sample of the study consists of 162 students at the School of Physical Education and Sports of Mardin Artuklu University. Internet addiction scale and Multiple Intelligences Self Evaluation Scale were used as data collection tools in the study. SPSS 20.0 package program was used in the analysis of the data obtained in the study. It was observed that data is normally distributed. Descriptive statistical analysis and correlation analysis were applied in the analysis of the data. At the end of the study, it was determined that there was a positive relationship between verbal intelligence and loss of control, and a negative relationship between the desire to be more online and the dimensions of negativity in social relations.